The impact of traumatic injury in the oil and gas industry. (January 2019) - Dang, Jerry T; Lester, Erica; Sun, Warren; Fawcett, Vanessa; Widder, Sandy; Tsang, Bonnie
Introduction: The oil and gas industry employs approximately 390, 000 people in Canada and these workers are often exposed to substantial workplace risks. Trauma centres treat a significant number of industry-related injuries; however, studies characterizing these traumatic events are lacking. Methods: A retrospective study was conducted of workers in the oil and gas industry admitted to major trauma centres in Edmonton, Alberta from January 2009 to December 2014. Patients were identified from Alberta Trauma Registry and Worker's Compensation Board data. Inclusion criteria were: age ≥16 years, trauma occurring in the oil and gas industry, and Injury Severity Score (ISS) ≥ 12 or Modified Abbreviated Injury Scale (MAIS) ≥ 3. Descriptive analysis and cost estimation were performed. Results: There were 182 major traumas occurring primarily in young males. Blunt trauma was the primary mechanism (90.1%), and alcohol levels were positive in 4.8% of patients. The overall complication rate was 32.4% with a mortality rate of 6%. The majority of patients were discharged home (64.3%), however a large proportion (29.7%) required further care at another facility post-acute care. The median days missed from work were 85 (IQR 7–214.5). Total cost of injury from the societal perspective ranged from 109 965 to 332 098 USD per person. Conclusion: Oil and gas industry trauma has a high economic and societal cost. Strategies to prevent injuries in this field should be undertaken including promotion and support of drug-free programmes given the rate of positive alcohol screening in this population.